Handbook of clinical psychopharmacology for therapists - Preston, John D.; O'Neal, John H.; Talaga, Mary C.; Moore, Bret A. (New Harbinger Publications, Inc., 2021)
"A comprehensive professional resource for mental health treatment--now in a fully revised and updated ninth edition The Handbook of Clinical Psychopharmacology for Therapists is the gold standard for mental health clinicians looking for clear, reliable information about the pharmacological treatment of mental health issues. Organized by disorder and, within each disorder, by medication, this book is designed to familiarize clinicians and students with the basic terminology and models of psychopharmacology. This fully revised and updated ninth edition provides essential information on new medications and treatment options and includes the latest research on side effects, contraindications, and efficacy of all major medications prescribed for mental health disorders. You'll also find new chapters on sleep disorders and experimental treatments, updated information on child and adolescent psychopharmacology and the latest best practices for treating pregnant and breastfeeding patients and patients with substance use disorders. This handbook makes it simple to: get the facts about drug interactions and side effects; find out how medications affect adults, children, and adolescents differently; learn how different cultures view medical treatment, vital information for anyone who treats clients from a variety of backgrounds; and discontinue medication safely when needed. This essential guide to psychopharmacology has been adopted as a textbook at universities nationwide and is an important resource for every therapist's library."--